Cadmans Cottage from the garden, Sydney Cove, Sydney, New South Wales, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting sandstone block, arch, windows, door, trees.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions document, see file NLA09/703.
Wes Stacey reference number: 5 17 6.
Also available online
Keywords: Cadman's Cottage (Sydney, N.S.W) -- Photographs; Arches -- New South Wales -- Sydney -- Photographs; Sandstone buildings -- New South Wales -- Sydney -- Photographs; Architecture, Colonial -- New South Wales -- Sydney -- Photographs; Architecture, Georgian -- New South Wales -- Sydney -- Photographs; Sydney (N.S.W.) -- Buildings, structures, etc. -- Photographs